Distinguishing gouty arthritis from calcium pyrophosphate disease and other arthritides - Löffler, Christian; Löffler, Uta; Tuleweit, Anika; Waldherr, Rüdiger; Uppenkamp, Michael; Bergner, Raoul (The journal of rheumatology, 2015)
Objective. Differentiating gout, calcium pyrophosphate deposition disease (CPPD), and non-crystal-related inflammatory arthropathies (non-CRA) is essential but often clinically impossible. The sonographic double contour (DC) sign may have good specificity for gout in highly specialized centers, but it can be challenging to use it to distinguish gout from cartilage hyperenhancements in CPPD. We evaluated the diagnostic value of the DC sign alone and in combination with Doppler signals and uric acid (UA) levels in patients with acute arthritis. Methods. We retrospectively investigated 225 acutely inflamed joints and documented the presence of DC, Doppler hypervascularization, and serum UA (SUA) levels. All patients underwent synovial fluid (SF) analysis. Sensitivity, specificity, and positive predictive values were calculated, and correlation analyses and a binary regression model were used to investigate their diagnostic values. Results. The sensitivity of DC sign for crystalline arthritides was 85% and specificity 80%. Its specificity for gout was 64%, for CPPD 52%. In contrast to non-CRA hypervascularization, degree 2 and 3 Doppler signals were highly associated with gout and less with CPPD (p < 0.01). The combination of DC sign with hypervascularization and elevated UA levels increased specificity for gout to more than 90% and resulted in a 7-fold increase of the likelihood of diagnosis of gout (p < 0.01), but with a loss of sensitivity (42%). Conclusion. The DC sign alone is suitable for predicting crystal-related arthropathies, but it cannot reliably distinguish gout from CPPD in everyday clinical routine. Combining hypervascularization and SUA levels increases the diagnostic value, leading us to propose a diagnostic algorithm.
Gesehen am 15.12.2017